(untitled) (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2025)
Tourism is reported to be one of the sectors contributing significantly to the high volume of waste generated daily in Bali. Beaches in Bali are inundated with large amounts of waste, particularly plastic waste. The issue of overtourism, which poses a threat to the tourism industry and the quality of life for Bali’s residents, has been acutely felt in one of Bali’s premier tourist destinations, Penglipuran Village in Bangli Regency. The people of Penglipuran Village have recognized the dangers posed by overtourism in their community. The management has formulated and implemented various strategies to mitigate the impact of overtourism. This study employs a qualitative descriptive method. The discussion focuses on the overtourism phenomenon in Penglipuran Village, the positive and negative impacts experienced by the local community, and the identification of at least twelve strategies that Penglipuran Village has implemented to address overtourism. These strategies aim to achieve sustainable tourism. Four indicators of success have been identified from the strategies applied by Penglipuran Village in handling overtourism. In maintaining sustainable tourism in Penglipuran Village, addressing overtourism has become a critical focus to balance tourism growth with environmental preservation and the safeguarding of local culture. This research aims to analyze the strategies and measures taken to overcome overtourism in Penglipuran Village, Bangli, with the goal of achieving sustainable tourism.